Advances in Clinical Audiology - Hatzopoulos, Stavros (IntechOpen, 2017)
Advances in Clinical Audiology is an excursus on the latest findings in clinical audiology with a strong emphasis in new emerging technologies which facilitate and optimize a better assessment of the human patient. The book has been edited with a strong educational perspective (all chapters include an extensive introduction to their corresponding topic and an extensive glossary of terms). The book contains material suitable for graduate students in audiology, ENT, hearing science, and neuroscience.